'A 40 years works feels / 40 more 40 thousand': Lionel Fogarty's hauntological poetics and the archive. Issue 11 (2nd November 2022) - Moore, Dashiell
ABSTRACT: This paper examines Yoogum and Kudjela poet Lionel Fogarty's commitment to define the terms in which his work will be remembered through close analysis of a range of archival materials gathered by Kalkadoon scholar Philip Morrissey and Tyne Daile Sumner for Lionel Fogarty's Selected Poems 1980–2017 (2017). I describe this component of his work as hauntology, a term picked up from Jacques Derrida's Spectres of Marx (1993) by Eve Tuck and Christopher Ree, who redefine hauntology as a 'relentless remembering and reminding that will not be appeased by settler society's assurances of innocence and reconciliation.' 1 In reference to these materials, I argue that Fogarty's poetry has a hauntological capacity to recall the moment of the poem's expression in endlessly cyclical processes so as to resist closure. By analysing the way these materials exemplify Fogarty's poetic principles, the paper anticipates a shift in the relationship between Aboriginal Australian writers and the literary archive.